2018
DOI: 10.1021/acssuschemeng.8b04180
|View full text |Cite
|
Sign up to set email alerts
|

Trimetallic (Co/Ni/Cu) Hydroxyphosphate Nanosheet Array as Efficient and Durable Electrocatalyst for Oxygen Evolution Reaction

Abstract: The construction of earth-abundant and non-noble-metal-based oxygen evolution reaction (OER) electrocatalysts that could work effectively with long-term stability in alkaline electrolyte is of primary significance, but still challenging. Herein, we propose a novel OER electrocatalyst based on trimetallic (Co/Ni/Cu) hydroxyphosphate with unique nanosheet array architecture grown on nickel foam, aiming at designing the non-noble-metal-based OER electrocatalyst with both excellent durability and catalytic activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“…As an excellent electrocatalyst, Fe 2.95 (PO 4 ) 2 (OH) 2 thin-film electrode exhibited an overpotential of 281 mV for OER (1 M KOH, 10 mA cm –2 ) and 165.7 mV for HER (1 M H 3 PO 4 , 10 mA cm –2 ), respectively [ 124 ]. As per previous reports, the TM-HP are commonly much more durable than the corresponding TM-phosphates in alkaline electrolytes [ 125 ]. For instance, Mani et al reported orthorhombic iron hydroxy phosphate (Fe 5 (PO 4 ) 4 (OH) 3 ·2H 2 O (FeHP)) synthesized by hydrothermal method from metal chloride precursors and disodium hydrogen phosphate as a source of phosphate ligand precursor (Fig.…”
Section: Electrocatalytic Performance Of Anion-mixed Electrocatalystssupporting
confidence: 67%
See 1 more Smart Citation
“…As an excellent electrocatalyst, Fe 2.95 (PO 4 ) 2 (OH) 2 thin-film electrode exhibited an overpotential of 281 mV for OER (1 M KOH, 10 mA cm –2 ) and 165.7 mV for HER (1 M H 3 PO 4 , 10 mA cm –2 ), respectively [ 124 ]. As per previous reports, the TM-HP are commonly much more durable than the corresponding TM-phosphates in alkaline electrolytes [ 125 ]. For instance, Mani et al reported orthorhombic iron hydroxy phosphate (Fe 5 (PO 4 ) 4 (OH) 3 ·2H 2 O (FeHP)) synthesized by hydrothermal method from metal chloride precursors and disodium hydrogen phosphate as a source of phosphate ligand precursor (Fig.…”
Section: Electrocatalytic Performance Of Anion-mixed Electrocatalystssupporting
confidence: 67%
“…In addition to the quaternary compound, the construction of trimetallic (Co/Ni/Cu) HP NSs on Ni foam has also been published. Zhang et al examined the design of CuHP loaded CoNi hybrid nanostructures by an ion exchanging method [ 125 ]. The excellent OER catalytic activity (a low overpotential of 370 mV at 50 mA cm –2 ) was mainly attributed to the high-valent cobalt species produced in situ during the electrooxidation process.…”
Section: Electrocatalytic Performance Of Anion-mixed Electrocatalystsmentioning
confidence: 99%
“…Figure 3c shows two peaks at 932.08 (Cu 2p 3/2 ) and 951.94 eV (Cu 2p 1/2 ), which indicates the existence of Cu 2+ in the catalyst. 21 Furthermore, high-resolution XPS spectrum of Se 3d (Figure 3d) also contains two chemical valence states, and the binding energies at 53.58 (Se 3d 5/2 ) and 54.38 eV (Se 3d 3/2 ) can be attributed to Se 1− , and the another peaks at 59.58 and 61.38 eV are attributed to Se 3− (Se 3d) − . 30 Figure 3e shows the O 1s, and the peak at 531.43 eV corresponds to the O−Cu bond, as well as a concomitant satellite at 532.93 eV.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…20 Meanwhile, relevant studies demonstrate that cross-linked multimetal structures can accelerate the halfreactions occurred in the water-splitting process. 21 For example, a 3D hierarchical MoSe 2 /NiSe 2 nanowires (NWs) show a high HER activity because the NiSe 2 phase is uniformly distributed in the MoSe 2 which promote the transfer rate of electrons from the active sites to the electrodes. 22 acid/alkaline electrolytes, causing unstable electrocatalytic performances of TMSs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Examples of trimetallic nanoparticles prepared this way include PdNiAl NPs, 178 NiFeCo NPs, 179 PtAgCu@PtCu core@shell concave nanooctahedrons as catalysts for formic acid oxidation, 180 (111)-terminated PtPdRh nanotruncated octahedrons for conversion of ethanol to CO 2 , 181 and CoNiCu hydroxyphosphate nanosheets as electrocatalysts for the oxygen evolution reaction. 182 …”
Section: Preparation Of Trimetallic Catalystsmentioning
confidence: 99%